Microbiological investigation of polyarthralgia. Issue 8 (August 1995) - Jones, J W; Pether, J V; Frost, R W
Abstract : Results of serological investigations on patients with joint pain, arthralgia or polyarthritis were analysed and this information was used to develop a diagnostic algorithm to ensure optimal utilisation of laboratory resources. Accordingly, all cases are now examined for parvovirus IgM, mycoplasma IgM and streptococcal antibodies. Further tests are undertaken by following the algorithm after obtaining supplementary information from a questionnaire. This approach is put forward as a preliminary standard which other laboratories may like to evaluate and develop according to local requirements.